THE IMPORTANCE OF TELEWORKING IN THE CONTEXT OF THE COVID-19 PANDEMIC (CIPEEX, 2025)
This research examines the significance of teleworking during the COVID-19 pandemic, when many professional activities could not be carried out in physical office settings due to social isolation. Through a bibliographic review, the study highlights how remote work allowed businesses to continue operating despite lockdown restrictions imposed by the government. Teleworking enabled workers to fulfill their responsibilities without needing to commute to the workplace, proving essential during this global public health crisis. The findings reveal that teleworking played a crucial role in maintaining employment and business operations, supported by technological advancements that minimized disruptions to business routines. The research concludes that the labor market has undergone significant transformations in recent years, largely due to the increasing integration of technology into businesses and society.
Keywords: Teleworking; Labor Law; Pandemic; Covid-19